2011
DOI: 10.3109/14767058.2011.592230
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity of fresh and stored breast milk: is −80°C optimal temperature for freeze storage?

Abstract: Freeze storage of breast milk at -80°C for two months seems not to be the optimal condition to preserve the antioxidant capacity of breast milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Meantime, different studies have divergent results for freezing, and the differences are not yet clear. This can be observed in studies such as Sari et al [4], in which the freezing of HM at -80°C reduced by 56.25% the antioxidant capacity of mature HM stored at -80°C for two months by the ABTS free radical scavenging method. On the other hand, Akdag et al [5] found no significant difference in the total antioxidant capacity of HM from mothers of preterm infants stored at -80°C for 3 months, also evaluated by the ABTS free radical scavenging method.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Meantime, different studies have divergent results for freezing, and the differences are not yet clear. This can be observed in studies such as Sari et al [4], in which the freezing of HM at -80°C reduced by 56.25% the antioxidant capacity of mature HM stored at -80°C for two months by the ABTS free radical scavenging method. On the other hand, Akdag et al [5] found no significant difference in the total antioxidant capacity of HM from mothers of preterm infants stored at -80°C for 3 months, also evaluated by the ABTS free radical scavenging method.…”
Section: Discussionmentioning
confidence: 69%
“…According to Akdag et al [5], the total antioxidant capacity of preterm HM was preserved at -80 °C for 3 months. However, according to Sari et al [4], the freezing samples of colostrum, transition and mature milk at -80 °C for two months did not preserve the antioxidant capacity. According to Hanna et al [6], the antioxidant capacity of HM also decreased with the storage time and refrigeration was better than freezing to preserve it, because the freezing for 48 hours caused greater losses than the refrigeration for seven days.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations